Charateristics of Settlement at Balikpapan Coastal Road Area (Case Study: Damai Regency) - Muhammad Hafid; Angga Danu Wibowo; Mila Karmilah; Wahyu Utami (International Conference on Coastal and Delta Areas, 2015)
Residential character influenced by its location. The settlements are located on thebeach would have been different with the existing settlements in the mountain valley, at the foot of the mountain or settlements in cities including settlements on the edge of the river. In addition to the formation of the land, the character of settlements is also influenced by the character of its inhabitants are much too influenced by the type of their livelihood. This paper describes the pattern of space that has occurred in the seaside settlement coastal road in District of Balikpapan City and district of South Balikpapan. The collecting data using descriptive qualitative method approach. This approach is at least able to describe the condition of settlement patterns that have occurred in the seaside coastal road including occupancy character from thestandpoint of livelihood of the population. Based on studies it is known that there are settlements along the shore coastal road that people whose live very heterogeneous, so the model that arrangement adapted to the understanding and ability of the community. Some proposals are doing structuring infrastructure existing environment, then in some areas is illegal land will be cultivated with the fulfillment of the towers (Rumah Susun) for low income. The characteristic of the settlement Damai Regency is likely most of many settlement in coastal area, that have a poor access for sanitation, the houses most build by wood and some of them rarely inundated by tidal flood.